A new powder encapsulation method and its implications on densification by hot isostatic pressing - Downing, M. (Cranfield University, 1993)
Hot isostatic pressing is now an accepted material processing technique for the consolidation of metal powders to near-net-shape components. This thesis examines the use of coatings as in-situ envelopes to overcome the problems associated with traditional containerisation of powder. The application of metallic coatings by physical vapour deposition, involving resistive and electron beam evaporation and ion plating, onto green powder metal compacts has been studied as a potential method for encapsulating powder metal products prior to hot isostatic pressing. The coating structures are discussed in terms of processing conditions and surface roughness influence. The most promising approach is a combined sinter-hot isostatic, pressing cycle, which utilises the formation of a transient liquid phase to defect-heal the coating during the sinter cycle prior to the application of pressure. The influence of particle size distribution on densification has also been studied. This included both monosized and bimodal powders. The results of this study has been incorporated into a modified Ashby model computer program and it is shown that the model results in a shift of the dominance of the mechanism fields and gives good correlation between the predicted and measured values of density.